Marcadores bioquímicos e hipertensión gestacional : utilidad del ácido ùrico como marcador de riesgo de las enfermedades de hipertensión inducidas por el embarazo - Corominas, Ana Irene (2017)
It is well known that preeclampsia is associated to high uric acid levels, but the clinical assessment of this relationship is still under consideration.\nOur aim was to describe the behavior of serum uric acid in pregnant woman and its possible role as an early predictor of gestational hypertensive pathologies to contribute to the care of pregnancy and childbirth.\nIn a retrospective study performed at the National Hospital "Dr. Prof. Alejandro Posadas ", we found that in the first half of gestation, uric acid levels were similar in normotensive pregnant women and in those who developed preeclampsia. However, after the 20th weeks of gestation, uric acid increases 1.5-fold in preeclamptic pregnant women, with no changes in uremia and creatininemia, confirming that these patients had no renal complications.\nIn a prospective approach, we found that the ratio of uricemia (after 20 weeks of gestation / before 20 weeks of gestation) has a high predictive negative value excluding these pathologies if the result is negative (<1,5) and high sensitivity if it is positive.\nOur findings suggest that uric acid is a candidate molecule for monitoring the risk of this group of pathologies.